In vitro tuberization of Chlorophytum borivilianum Sant & Fern (Safed musli) as influenced by sucrose, CCC and culture systems - Ashraf, Mehdi Farshad; Abdul Aziz, Maheran; Abdul Kadir, Mihdzar; Stanslas, Johnson; Farokhian, Elmira (Oxford University Press, 2013)
This study focuses on the establishment of in vitro tuberization of Chlorophytum borivilianum using solid and liquid culture systems. A high in vitro tuberization rate on solid and stationary liquid Murashige and Skoog media was observed in the presence of 60 g l−1 sucrose with 950, 1,265 and 1,580 µM 2-chloroethyl-trimethylammonium chloride (CCC). Application of a higher sucrose concentration of 90 g l−1 showed a negative interaction with CCC on in vitro tuber number and days to in vitro tuber induction. For economic feasibility, 950 µM CCC with 60 g l−1 sucrose was chosen as the best combination for in vitro tuberization in both solid and stationary liquid media. For optimization of in vitro tuber production, a comparison between solid, stationary liquid and shake liquid culture was carried out. Liquid culture with shaking at 80 r.p.m. resulted in a >2.5-fold increase in in vitro tuber production compared with solid culture.